2023
DOI: 10.1021/acs.inorgchem.3c00724
|View full text |Cite
|
Sign up to set email alerts
|

Vanadyl as a Spectroscopic Probe of Tunable Ligand Donor Strength in Bimetallic Complexes

Abstract: Incorporation of secondary metal ions into heterobimetallic complexes has emerged as an attractive strategy for rational tuning of compounds' properties and reactivity, but direct solution-phase spectroscopic interrogation of tuning effects has received less attention than it deserves. Here, we report the assembly and study of a series of heterobimetallic complexes containing the vanadyl ion, [VO] 2+ , paired with monovalent cations (Cs + , Rb + , K + , Na + , and Li + ) and a divalent cation (Ca 2+ ). These c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(23 citation statements)
references
References 91 publications
1
22
0
Order By: Relevance
“…Similar features were measured for all the heterobimetallic species, albeit shifted in each case to higher energies, similar to observations made in prior work (see Figures S40−S66). [8][9][10]34 Upon cation incorporation, both the d−d and CT transitions undergo blue shifts relative to the precursor complex [Ni]. As shown in Figure 4, the CT transitions undergo a shift from 418 nm for [Ni] to 370 nm for [Ni,La], whereas the d−d transitions shift more modestly from 550 to 535 nm for the same range of complexes as can be seen in [ 33,35 Electrochemical Studies.…”
Section: Synthesis and Characterizationmentioning
confidence: 54%
See 2 more Smart Citations
“…Similar features were measured for all the heterobimetallic species, albeit shifted in each case to higher energies, similar to observations made in prior work (see Figures S40−S66). [8][9][10]34 Upon cation incorporation, both the d−d and CT transitions undergo blue shifts relative to the precursor complex [Ni]. As shown in Figure 4, the CT transitions undergo a shift from 418 nm for [Ni] to 370 nm for [Ni,La], whereas the d−d transitions shift more modestly from 550 to 535 nm for the same range of complexes as can be seen in [ 33,35 Electrochemical Studies.…”
Section: Synthesis and Characterizationmentioning
confidence: 54%
“…This relationship could be indicative of charge density effects being operative in this system, wherein the cationic charge of the secondary cations exerts an electrostatic influence over, of primary importance, the phenoxide moieties that bridge to the nickel center. 10,38 In such a case, the phenoxide O atoms could be subject to an influence from the secondary metal cations that is not unlike the influence cast over the coordinated water molecules in the metal−aqua complexes for which the pK a values were tabulated. 16 EPR Studies.…”
Section: Synthesis and Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In order to generate isolable uranyl-crown complexes, we developed a Pt­(II)-templated macrocycle (denoted 1 ) with a Reinhoudt-type ligand scaffold that presents an 18-crown-6-like site for binding of the uranyl ion, UO 2 2+ . In prior work, we have used crown-containing ligands to access lanthanide-binding Ni­(II), Pd­(II), Zn­(II), and V­(IV) , complexes, but here, a new method was developed for installation of a platinum center into the macrocyclic framework with the goal of imparting stability and enabling future spectroscopic studies with 195 Pt NMR (see Experimental Section in Supporting Information for details). We found that 1 could be prepared from the previously reported [H 2 ,Ba] using Ba­(OH) 2 ·8H 2 O as a base and Pt­(DMSO) 2 Cl 2 as a metalating agent (Scheme ).…”
Section: Resultsmentioning
confidence: 99%
“…One of the more broadly studied effects of Lewis acids on electron transfer involves the conjugation of redox-active metal complexes to crown-ethers (Figure ). Extensive studies on mono- ( 1 ) and bimetallic ( 2 ) manganese Schiff-base complexes first appeared in the 1990s that aimed to elucidate the properties of manganese-dependent enzymes (including the OEC). While salen-type related ligands have been shown to be useful for binding or sensing of a wide variety of redox-inactive metals via coordination to O atom donors (e.g., phenoxide), inclusion of crown-ether motifs enables stronger binding of Lewis acidic ions with stoichiometric control. Exposing complex 1 to Li + , K + , Ca 2+ , or Ba 2+ leads to incorporation of a single redox-inactive metal into the crown-ether moiety, resulting in a positive shift in reduction potential for the Mn III /Mn II redox couple .…”
Section: Electron Transfer and Lewis Acidsmentioning
confidence: 99%